2019
DOI: 10.1177/1440783319837609
|View full text |Cite
|
Sign up to set email alerts
|

Student debt, neoliberalism and frame analysis: A Goffmanesque account of neoliberal governmentality

Abstract: Ballooning levels of student debt have manifested as an important and global social problem and highlight long-standing forms of governmentality. It is our contention that while Foucaldian, top-down analysis provides a valid account of prevailing governmentality, it may not be as sensitive to ambiguity wherein moral subjects are not unproblematically the risk-taking entrepreneurs that neoliberalism requires. This ambiguity is around debt, and relates to the definition of student debt as good debt or bad debt. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…University students in Australia are incurring increasing levels of debt to attain a degree and there is a direct relationship between education-income-debt: the better educated you are, the more you earn; the more you earn, the more likely you are to hold debt and the more debt you are likely to hold (ABS, 2017). Higher education in Australia, as in other similar countries, operates under a neoliberal market logic as its primary informing framework and has done so since the 1980s (Etherington, 2016;Kanade & Curtis, 2019). The introduction of higher education student fees (initially 'contributions' but later 'loans') in 1989 are a feature of this logic, designed to shift the financial burden of higher education from the state to students (Jackson, 2003).…”
Section: The Mortgage-education-debt-work Nexusmentioning
confidence: 99%
“…University students in Australia are incurring increasing levels of debt to attain a degree and there is a direct relationship between education-income-debt: the better educated you are, the more you earn; the more you earn, the more likely you are to hold debt and the more debt you are likely to hold (ABS, 2017). Higher education in Australia, as in other similar countries, operates under a neoliberal market logic as its primary informing framework and has done so since the 1980s (Etherington, 2016;Kanade & Curtis, 2019). The introduction of higher education student fees (initially 'contributions' but later 'loans') in 1989 are a feature of this logic, designed to shift the financial burden of higher education from the state to students (Jackson, 2003).…”
Section: The Mortgage-education-debt-work Nexusmentioning
confidence: 99%
“…Supporting the students through smartphone loans or any other loans is also putting them under stress about their future loan repayment. Kanade and Curtis (2019) argued that student debt is forcing students to become neoliberal subjects and increasing inequality in society. Giroux (2020) argued that neoliberalism is destroying our democratic values by forcing us to ignore the social context.…”
Section: Effect Of Policy Responsementioning
confidence: 99%
“…The current university system is shaped by a neoliberal economic and cultural regime -specifically, the establishment of academic capitalism (Slaughter and Rhoades, 2004). Scholars have shown that, perhaps unexpectedly and not without resistance, utilitarian attitudes now dominate university organisational culture, as well as teaching and learning approaches (Deem and Johnson, 2003;Brooks et al, 2016;Hyatt et al, 2015;Posecznick, 2017;Wright and Shore, 2017;Kanade and Curtis, 2019). Concomitantly, the marketisation and commercialisation of academia bring with them a powerful emotional aspect.…”
mentioning
confidence: 99%